γ-Selective Directed Catalytic Asymmetric Hydroboration of 1,1-Disubstituted Alkenes() - Smith, Sean M. (2012)
Directed catalytic asymmetric hydroborations of 1,1-disubstituted alkenes afford γ-dioxaborato amides and esters in high enantiomeric purity (90–95% ee).